Globalization and the new politics of embedded liberalism - Hays, Jude C. (New York ; Oxford : Oxford University Press, 2009)
This book explores how domestic institutions shape the ways governments redistribute the risks and benefits of economic globalization, identifying the Anglo-American democracies because of their majoritarian polities and decentralized competitive economies, as uniquely vulnerable to the challenges of globalization.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Liberalism; Globalization -- Political aspects